Populism in Poland – between demagoguery and demophilia - Kasprowicz, Dominika; Hess, Agnieszka (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
The goal of this paper is to present the evolution of populism in Poland using the examples of two political parties: the “Samoobrona” (“Self-Defense”) political party of Andrzej Lepper (a populist party which garnered most support in the first decade of the 21st century) and the “Kukiz ‘15” movement – the dark horse of the last Polish parliamentary elections. Both of these groups superbly illustrate the demagogy characteristic of populism, linked with an affirmation of the people (nation) which in turn would not be possible without the anti-establishment stance of the political leaders and the electorate. A comparison of these two examples al- lows us to monitor the transformations occurring in populist groups over the last few years, especially in the age where the Internet is employed as a vital means of communication. The paper presents the alternative conceptualizations of the idea of populism, and moves on to employ the N. Baar scheme (2009) and secondary and primary data (data obtained from the “Barometr Wyborczy” voting advisory application), and press releases to draft various types of correspondence between these two cases, which makes it possible to identify new, interesting characteristics of populism.

Celem artykułu jest przedstawienie ewolucji populizmu w Polsce przy użyciu dwóch przykładów partii politycznych: „Samoobrony” Andrzeja Leppera (była to partia populistyczna, która uzyskała największe poparcie w pierwszej dekadzie XXI wieku) oraz ruchu „Kukiz’15” – czarnego konia ostatnich wyborów parlamentarnych. Oba te ugrupowania znakomicie ilustrują demagogię charakterystyczną dla populizmu, związaną z afirmacją narodu, która z kolei nie byłaby możliwa bez anty-establishmentowej postawy przywódców politycznych i elektoratu. Porównanie tych dwóch przykładów umożliwiło nam monitorowanie przemian zachodzących w ugrupowaniach populistycznych w ciągu ostatnich kilku lat, zwłaszcza w czasach gdy Internet służy jako podstawowy środek komunikacji. W artykule zaprezentowano kolejno alternatywne konceptualizacje idei populizmu, a później – korzystając ze schematu N. Baara (2009) i danych drugorzędnych i podstawowych (dane uzyskane w internetowym poradniku wyborczym „Barometr Wyborczy”), oraz publikacji prasowych – zarysowano różnorodne powiązania występujące między obydwoma ugrupowaniami, co pozwoliło w rezultacie określić nowe, ciekawe cechy populizmu.
Populizm w Polsce – między demagogią i demofilią
Keywords: populism; party politics in Poland; Poland; populizm; partie polityczne w Polsce; Polska